Why do stroke survivors not receive recommended amounts of active therapy? Findings from the ReAcT study, a mixed-methods case-study evaluation in eight stroke units. (August 2018) - Clarke, David J; Burton, Louisa-Jane; Tyson, Sarah F; Rodgers, Helen; Drummond, Avril; Palmer, Rebecca; Hoffman, Alex; Prescott, Matthew; Tyrrell, Pippa; Brkic, Lianne; Grenfell, Katie; Forster, Anne
Objective: To identify why the National Clinical Guideline recommendation of 45 minutes of each appropriate therapy daily is not met in many English stroke units. Design: Mixed-methods case-study evaluation, including modified process mapping, non-participant observations of service organisation and therapy delivery, documentary analysis and semi-structured interviews. Setting: Eight stroke units in four English regions. Subjects: Seventy-seven patients with stroke, 53 carers and 197 stroke unit staff were observed; 49 patients, 50 carers and 131 staff participants were interviewed. Results: Over 1000 hours of non-participant observations and 433 patient-specific therapy observations were undertaken. The most significant factor influencing amount and frequency of therapy provided was the time therapists routinely spent, individually and collectively, in information exchange. Patient factors, including fatigue and tolerance influenced therapists' decisions about frequency and intensity, typically resulting in adaptation of therapy rather than no provision. Limited use of individual patient therapy timetables was evident. Therapist staffing levels were associated with differences in therapy provision but were not the main determinant of intensity and frequency. Few therapists demonstrated understanding of the evidence underpinning recommendations for increased therapy frequency and intensity. Units delivering more therapy had undertaken patient-focused reorganisation of therapists' working practices, enabling them to provide therapy consistent with guideline recommendations. Conclusion: Time spent in information exchange impacted on therapy provision in stroke units. Reorganisation of therapists' work improved alignment with guidelines.